New species and record of Diplosmittia Sæther, 1981 (Diptera: Chironomidae, Orthocladiinae) from Brazil and Colombia - Dantas, Galileu P.s.; Amat, Eduardo; Hamada, Neusa (Zootaxa, 2024)
Chironomidae is a diverse Diptera family found worldwide. The genus Diplosmittia Sæther, 1981, currently with 11 valid species, has been found exclusively in the New World, mainly in the Caribbean and in the northern parts of South America; only three species are recorded from Brazil and none from Colombia so far. In the present study a new species of Diplosmittia is described and illustrated based on material collected in northeastern Brazil. It appears to be most closely related to Diplosmittia beluina Andersen, 1996, but can be distinguished by morphological differences in the virga and gonostylus. Diplosmittia harrisoni Sæther, 1981 is documented for the first time from Colombia, and D. carinata Sæther, 1985 is formally placed as a junior synonym of D. harrisoni. In addition, an update identification key to all known species of the genus has been provide.